2010
DOI: 10.1007/s11126-010-9155-x
|View full text |Cite
|
Sign up to set email alerts
|

The Violence Triad and Common Single Precipitants to Psychiatric Patient Assaults on Staff: 16-Year Analysis of the Assaulted Staff Action Program

Abstract: Psychiatric patient assaults are a serious community health hazard. Risk management strategies to identify common single precipitants have had limited value and this limitation has resulted in the emergence of multiple determinant studies. This 16-year retrospective study of assault precipitants in one, public sector mental health-care system assessed single common, immediate precipitants; the multiple clinical precipitants of history of violence, personal victimization, and substance use disorder (the violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
(52 reference statements)
1
26
0
1
Order By: Relevance
“…19 In a 16-year observational study, acute psychosis precipitated 19% of physical and verbal assaultive behaviors by psychiatric inpatients. 20 Contrary to the common belief that patient violence occurs without warning, [21][22][23][24] most violent episodes are preceded by specific behavioral warning signs and cues, 1-6 such as explosive or unpredictable anger, intimidation, restlessness, pacing and excessive movement, physical or verbal self-abusiveness, verbally demeaning or hostile behavior, uncooperative or demanding behavior, and impulsiveness and impatience. 9 In 1992, Morrison observed that psychiatric inpatients' aggressive and violent behaviors occurred along a hierarchy of eight levels (Table 1), with higher levels indicating more severe aggression.…”
Section: Predictors Of Psychiatric Inpatient Aggression and Violencementioning
confidence: 99%
“…19 In a 16-year observational study, acute psychosis precipitated 19% of physical and verbal assaultive behaviors by psychiatric inpatients. 20 Contrary to the common belief that patient violence occurs without warning, [21][22][23][24] most violent episodes are preceded by specific behavioral warning signs and cues, 1-6 such as explosive or unpredictable anger, intimidation, restlessness, pacing and excessive movement, physical or verbal self-abusiveness, verbally demeaning or hostile behavior, uncooperative or demanding behavior, and impulsiveness and impatience. 9 In 1992, Morrison observed that psychiatric inpatients' aggressive and violent behaviors occurred along a hierarchy of eight levels (Table 1), with higher levels indicating more severe aggression.…”
Section: Predictors Of Psychiatric Inpatient Aggression and Violencementioning
confidence: 99%
“…Secondly, this study's findings again document high levels of violence toward others, personal victimization, and substance use disorder as all being present in many assaultive patients. Previous research [24] has demonstrated that the presence of these three clinical variables taken together is highly associated with subsequent assault and care givers should be alert, when these variables are present in patients. Thirdly, these present findings continue to document unacceptable levels of violence committed against women in society [1,16].…”
Section: Specific Clinical Findingsmentioning
confidence: 99%
“…Thus, the estimates of prevalence and risk of violent behavior in the community are lowered by a constant removal of the most violent schizophrenia patients to hospitals and jails. In many cases, violent behavior continues inside these institutions [30,31]. Furthermore, it is important to point out that only some incidents of aggressive behavior lead to prosecution.…”
Section: Prevalence Of Violent Behavior In Schizophreniamentioning
confidence: 99%